Strategi Pemerintah Provinsi Sumatera Barat dalam Mengembangkan e-Government sebagai Upaya Peningkatan Kualitas Pelayanan Publik - Yoserizal Yoserizal; Wahyu Eko Yudiatmaja (JIANA ( Jurnal Ilmu Administrasi Negara ), 2010)
The development of information and communication technology is faster to give someeastness for human life. Because of the advanced of information technology, government candevelop public service in information technology. This technology is called by e-Government. Inregional contects, by spirit of regional autonomy wich give democratized and autonomy to region,the Government of West Sumatera Province also try to develope e-Government as one of the effortto improving public service quality. Approachment or metode used is qualitative with descriptivetype. The process of submiting data done by using interview and documentation done in someinstantion in environment of the Government of West Sumatera Province. The technic of informanchoosing used is purposive sampling. Data is analyzed by using etic and emic analyze. Theresearch result show that the strategy of Government of West Sumatera Province in developing e-Government as one of effort of improving public service quality by earlier analyzing the environ-ment of organization strategic. The strategy is: 1) Comparative Advantage Strategy; (a) Releasingproduct of regional law as law background of e-Government development, (b) Pointing PublicRelationship Bureau as work unit manufacturer of e-Government development, 2) Investment/Divestment Strategy; (a) Adding a number of employee program and giving guidance and trainingto improve employee quality, (b) Pointing some employees to manufacture e-Government on eachSKPD, (c) Selecting unurgent programs and plan optimalized, 3) Mobilization Strategy; (a) Build-ing strong system, and 4) Damage Control Strategy; (a) Cooperating with involved institution incentral.